Increasing the focus on critical appraisal of trials and financial conflict of interest in medical training programs: a perspective from oncology - Duits, Ashley J.; Samson, Michael J.; Gans, Rijk O. B.; Gerstenbluth, Izzy; Busari, Jamiu O.; Schnog, John-John B. (Frontiers in Medicine, 2025)
Improving medical education programs is key for achieving true value-based healthcare. Worldwide several approaches have been proposed for adapting current medical curricula in order to better foster modern medical professionals as agents of change. Adaptations of (mostly) competency-based curricula include improved attention for topics like public health, social determinants of health, inclusivity and social justice. In this article the authors argue, using an oncology perspective, for inclusion of two key topics in order to ensure that improved medical curricula foster critical consciousness and are transformative. The authors describe the importance of adding critical trial appraisal and awareness of the challenges of financial conflict of interest (FCI) in medical decision making throughout the curriculum. In the field of oncology (as in other medical areas) approval and uptake in treatment guidelines of costly drugs are regularly based on methodologically flawed clinical trials. Moreover, in an already financially strained environment these low-value treatments further impede countries of better supporting only high-value treatment and prevention programs. The authors show that FCI negatively impacts drug approval processes, journal publications, guideline inclusion and patient advocacy group activities. In this scholarly perspective the authors strongly argue for including these topics in modern curricula with due attention for the necessary cultural change of faculty and clinical learning environment. An educational moonshot program based on critical pedagogy is advocated in which both High Income Countries (HIC) and Low- and Middle-Income Countries (LMIC) contribute to achieve the necessary transformative medical education programs necessary for the required agents of change.